Increased Articular Exposure of the Lateral Tibial Plateau with a Midline Lateral Parapatellar Arthrotomy Compared to an Anterolateral Submeniscal Arthrotomy: a Cadaveric Study. Issue 8 (August 2021) - Rinehart, Dustin; Starr, Adam; Sanders, Drew; Cutler, Holt; Gross, Bruno; Hull, Brandon; Sathy, Ashoke
Highlights: Quantitative comparison of articular exposure with a lateral parapatellar arthrotomy and submeniscal arthrotomy. Average articular surface area exposed was 2.2 times greater through midline approach compared with lateral parapatellar arthrotomy. Improved exposure with midline approach may allow better visualization of the lateral plateau posteromedial quadrant. ABSTRACT: Purpose: To quantitatively compare the articular exposure of the proximal tibia with a lateral parapatellar arthrotomy through a straight midline incision (ML) versus a lateral submeniscal arthrotomy through a curvilinear anterolateral incision (AL). Methods: Eight surgical approaches (4 ML and 4 AL) were performed on 4 fresh cadavers. Access to key articular landmarks was assessed, including divisions of the lateral meniscus, lateral tibial spine, and anterior cruciate ligament. The boundary of the exposed articular surface of the tibia was marked, and the proximal tibias were then stripped of soft tissues. A calibrated digital image was taken of each proximal tibia, and exposed articular surface area was calculated with ImageJ software (NIH, Bethesda, MD). Statistical analysis was performed using a two-sample t-test. Results: Average articular surface area exposed was 2.2 times greater through the midline approach compared with the anterolateral approach (11.2 vs 5.1 cm 2, p = 0.010). All key anatomic landmarks were directly visualized through the midline approach in each specimen. Complete visualization of the lateral meniscus posterior horn, lateral tibial spine, and anterior cruciate ligament was not accomplished through the anterolateral approach in any specimen. Conclusions: The midline approach provides more extensive articular exposure of the lateral tibial plateau compared with the anterolateral approach. This improved exposure may offer an advantage when treating fractures not amenable to arthroscopic or minimally invasive techniques. It may be of most use when treating fractures with extension into the posteromedial quadrant of the lateral plateau, fractures with extensive comminution of the lateral plateau, or fractures with complex lateral meniscus tears and fractures with tibial spine involvement.